Fostering Divergent Thinking in the Classroom: The Impact of Project-Based Learning on Student Creativity - Harianta Sembiring; Nofirman Nofirman; Fini Widya Fransiska; Wahju Dyah Laksmi Wardhani; Rina Farah (Journal of Loomingulisus ja Innovatsioon, 2025)
The growing demand for 21st-century skills underscores the importance of nurturing students’ creativity through educational practices that promote divergent thinking. This study investigates the impact of Project-Based Learning (PBL) on fostering divergent thinking and creative performance among high school students. The research aims to analyze how the integration of PBL facilitates idea fluency, flexibility, originality, and elaboration in learners’ creative processes. A quasi-experimental design was employed, involving two groups of students: one receiving traditional instruction and the other exposed to PBL interventions across four project cycles. Data were collected using a validated creativity assessment rubric and analyzed through descriptive and inferential statistics (ANOVA). The findings reveal a significant improvement in divergent thinking indicators among students taught through PBL, particularly in their ability to generate multiple and original ideas. Qualitative observations also highlight that collaborative project environments enhanced motivation, self-expression, and problem-solving capacities. The study concludes that PBL serves as an effective pedagogical framework for cultivating creative and divergent thinking skills essential for innovation-driven learning. Implications emphasize the need for curriculum designers and educators to embed authentic, project-based tasks within classroom instruction.